Pituitary society expert Delphi consensus: operative workflow in endoscopic transsphenoidal pituitary adenoma resection - Marcus, Hani J.; Khan, Danyal Z.; Borg, Anouk; Buchfelder, Michael; Cetas, Justin S.; Collins, Justin W.; Dorward, Neil L.; Fleseriu, Maria; Gurnell, Mark; Javadpour, Mohsen; Jones, Pamela S.; Koh, Chan Hee; et al. (Pituitary, 2021)
Purpose: Surgical workflow analysis seeks to systematically break down operations into hierarchal components. It facilitates education, training, and understanding of surgical variations. There are known educational demands and variations in surgical practice in endoscopic transsphenoidal approaches to pituitary adenomas. Through an iterative consensus process, we generated a surgical workflow reflective of contemporary surgical practice. Methods: A mixed-methods consensus process composed of a literature review and iterative Delphi surveys was carried out within the Pituitary Society. Each round of the survey was repeated until data saturation and > 90% consensus was reached. Results: There was a 100% response rate and no attrition across both Delphi rounds. Eighteen international expert panel members participated. An extensive workflow of 4 phases (nasal, sphenoid, sellar and closure) and 40 steps, with associated technical errors and adverse events, were agreed upon by 100% of panel members across rounds. Both core and case-specific or surgeon-specific variations in operative steps were captured. Conclusions: Through an international expert panel consensus, a workflow for the performance of endoscopic transsphenoidal pituitary adenoma resection has been generated. This workflow captures a wide range of contemporary operative practice. The agreed “core” steps will serve as a foundation for education, training, assessment and technological development (e.g. models and simulators). The “optional” steps highlight areas of heterogeneity of practice that will benefit from further research (e.g. methods of skull base repair). Further adjustments could be made to increase applicability around the world.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Consensus; Delphi; Endoscopic endonasal; Endoscopic transsphenoidal surgery; Pituitary; Pituitary adenoma; Skull base surgery